Fiscal multipliers for Bosnia and Herzegovina - Dragana Staniésić; Belma Hadžihalilović-Kasumović (Graduate Institute of International and Development Studies, 2017)
The aim of this paper is to determine the size of fiscal multipliers (spending and tax multipliers) using a structural vector autoregressive model for Bosnia and Herzegovina (BiH). This is the first attempt of its kind for the BiH economy. The results show that the spending multiplier is higher than the tax multiplier, as expected. The tax multiplier has a negative effect on output and does not have any positive effects on other variables. The spending multiplier has positive effects, but they are limited to the first year after the shock. Both multipliers are within the set of values obtained in other studies on emerging economies.
Keywords: 330